Expert Internet Searching - Bradley, Phil (Facet Publishing, 2017)
In an environment where increasing amounts of information (and fake news) flood the internet on websites and social media, the information professional's job is getting harder. It is important that they are skilled at finding and using the appropriate information and assisting users in working out what information they need and the best way of getting it. Expert Internet Searching provides library and information professionals with in-depth practical information on how to search the internet quickly and effectively to help their users and make their lives easier. Now fully revised for its fifth edition, this book covers the basics of search before going into detail on how to run advanced and complex searches using a variety of different search engines. This edition has been updated to include current trends in search, such as social media search, fake news, and discussion of the authority and validity of search results. It will ensure that information professionals, whether complete beginners or more experienced, are able to work efficiently to obtain accurate information in a timely fashion.